Cognitive behavioral therapy for ADHD predominantly inattentive presentation: randomized controlled trial of two psychological treatments - Strålin, Elinor Eskilsson; Thorell, Lisa B.; Lundgren, Tobias; Bölte, Sven; Bohman, Benjamin (Frontiers in Psychiatry, 2025)
IntroductionAttention-Deficit Hyperactivity Disorder (ADHD) in adults is common and characterized by difficulties in regulation of attention, activity and goal directed behaviors. These challenges are especially associated with inattentive symptoms, why high levels of inattention imply severe impairment in everyday life. CBT for ADHD-inattentive presentation, (CADDI), is designed to treat inattention and incorporates skills training in organization, behavioral activation, and mindfulness. The aim of this study was to compare the effectiveness of CADDI with regular CBT treatment for ADHD.MethodsA multicenter, pragmatic, two-arm, parallel, randomized controlled trial compared CADDI to Hesslinger’s dialectical behavior therapy protocol. The study included 108 participants from six psychiatric outpatient clinics in Stockholm. Self-reported scales were used to assess outcome measures of behavioral activation, procrastination, symptoms of ADHD, depression, quality of life and functional impairment. Data were analyzed for between and within-group effects using multilevel modeling.ResultsBetween-group analysis showed that participants in the CADDI group had significantly greater improvement on the primary outcome measure of activation at post assessment (p = .045, d = 0.49). No significant between-group effect was found on the other measures. However, within-group analysis showed larger effect sizes in the CADDI condition relative to the control condition on several measures. Adherence was good and attrition 21.3% despite effects of the pandemic. Participants and therapists reported higher satisfaction with CADDI as compared to the control group.DiscussionThis trial demonstrated that CADDI was more effective regarding behavioral activation and suggests a potential advantage of an intervention specifically targeting ADHD-I over generic CBT for ADHD. However, the trial was underpowered and failed to prove between-group effects in spite of large differences in effect sizes on several measures. Future research with larger samples and long-term follow-ups is recommended to validate and expand upon these results.